(untitled) - Rickard, Sean (Maidenhead, 2006)
To operate as a successful manager requires an economic way of thinking, in particular a clear focus on efficiency and the working of markets. "The Economics of Organizations and Strategy" integrates business strategy within an economics framework, to give an economic perspective on areas of business such as organizational behaviour, marketing, finance, human resources and operations management. The book opens with an explanation as to how microeconomic theories and concepts relate to the organisational structures of firms and their strategies. It then builds on this introduction to show how these concepts relate to the boundaries, growth and management of firms. Having examined the inner workings of firms it then moves on to analyse their strategic behaviour and the influence of industry structure, product differentiation and R&D.Key features of this book include: coverage of European competition policy; integration of economic and game theoretic models to demonstrate strategic conflict and cooperation; up-to-date business examples to demonstrate the application of theory in a 'real-world' context; exercises that encourage students to work through business problems relevant to a prospective management role; and, a clear writing style that presents complex ideas in an accessible manner.
Keywords: Business enterprises,Business planning,Microeconomics,Kinh tế vi mô,Lập chiến lược kinh doanh,Tổ chức kinh doanh; Economic aspects,Khía cạnh kinh tế